Synthesis Memantine and Memantine Hydrochloride by Direct Amination of 1-Bromo-3,5-dimethyladamantane with Thiourea - Nguyen, Thi Hong T.; Vu, Binh Duong; Phan, Dinh Chau; Nguyen, Thi Hong Thanh; Luong, Quang Anh; Ngo, Thi Xuan Thu (Letters in Organic Chemistry, 2023)
Memantine hydrochloride (MH) is a first-line therapeutic drug approved by the US FDA for the management of moderate to severe Alzheimer's disease. This study involves the synthesis of memantine hydrochloride from 1-bromo-3,5-dimethyladamantane through a reaction with thiourea. The research results showed that the solvent reaction was propylene glycol (PG); the total time reaction was 5.5 hours, the temperature reaction in the first stage was 160°C and in the second stage was 80°C; the overall yield was 82.44%. The reaction intermediates were confirmed by the IR, MS,1HNMR, and 13C-NMR spectra.
Keywords: synthesis